Makna Denotatif dan Konotatif dalam Lirik Lagu Karya Bernadya: Kajian Semantik: Denotative and Connotative Meanings in Song Lyrics by Bernadya: A Semantic Study - Vidilah Lu'lu'watun Halsa; Dian Karina Rachmawati; Insani Wahyu Mubarok (Information Technology and Science(ITScience), 2026)
This article aims to describe the denotative and connotative meanings in the lyrics of Bernadya's songs entitled Lama-Lama, Ambang Pintu, and Kata Mereka Ini Berlebihan, using lexical-semantic analysis based on Chaer's (2013) theory. This study uses a qualitative descriptive method because it focuses on the meaning of language contained in song lyrics. The data collection technique is carried out through the listening and noting method, namely by carefully listening to the song lyrics and noting words, phrases, and sentences that convey denotative and connotative meanings. The research data sources are three songs by Bernadya, chosen for their rich, meaningful lyrics and descriptions of emotional experiences in romantic relationships. The results show that the three songs tell the story of someone who makes various sacrifices to maintain a romantic relationship. These sacrifices include understanding one's partner, even though it is not the main priority; giving a second chance to repair a strained relationship; changing oneself to meet the partner's expectations; and sacrificing time, energy, and feelings. Denotatively, these lyrics describe real actions taken in a romantic relationship. Meanwhile, connotatively, the lyrics convey loyalty, sincerity, sacrifice, and hope for a lasting relationship. Thus, the language used in Bernadya's lyrics demonstrates a richness of meaning, conveying profound emotional experiences through simple yet meaningful word choices. This research is expected to contribute to the development of semantic studies, particularly the analysis of meaning in song lyrics.